Legal Policy on the Flexibility of Establishing State Ministries for the Implementation of Government - Martha Riananda; Ahmad Saleh; Malicia Evendia; Ade Arif Firmansyah (Progressive Law Review, 2025)
The amendment to Law Number 39 of 2008 concerning State Ministries has sparked controversy in society, particularly regarding the flexibility of the number of ministries, which is no longer limited. When a legal norm undergoes regulatory changes, there is certainly a background. Law Number 61 of 2024, issued amidst the government's “efficiency” agenda, is an interesting anomaly to study. This study aims to identify and analyze the legal politics of the flexibility of the formation of state ministries in relation to government administration. This research employs a normative, utilizing a statutory, philosophical, conceptual, and case-based approach, framework to examine laws and legal phenomena. The results of this study, namely the legal politics of the flexibility of the formation of state ministries, which was originally limited to a maximum of 34 (thirty-four) ministries, then changed to "unlimited", indicate an attempt to actualize the strengthening of the President's prerogative, which does not require restrictions on ministerial institutional organs. The change in legal norms does not lead to a reduction in the number of ministries, but to an increase in the number of ministries. Law Number 61 of 2024 does not regulate substantive criteria for the formation of the number of ministerial organs, through the clause “needs for the administration of government by the President”, thus giving the President great discretion to determine how many ministerial organs are needed in the administration of government affairs.